Assessment of diagnostic and therapeutic vitrectomy for vitreous opacity associated with uveitis with various etiologies. Issue 2 (January 2018) - Sato, Tomohito; Kinoshita, Rina; Taguchi, Manzo; Sugita, Sunao; Kaburaki, Toshikatsu; Sakurai, Yutaka; Takeuchi, Masaru
Abstract : Abstract: Vitreous opacity (VO) is a common feature of intermediate uveitis, posterior uveitis, and panuveitis. Fundus observation is critical for determining the etiology of uveitis, however, is often interfered with VO. In these clinical settings, vitrectomy contributes to a correct diagnosis and guides alternative management strategies. The purpose of this study was to evaluate the diagnostic yield and surgical outcome of vitrectomy in uveitic patients with VO and compare the visual outcome between infectious and noninfectious uveitis. Forty-five eyes with uveitis-associated VO underwent diagnostic and therapeutic vitrectomy, and etiological diagnosis of uveitis was confirmed in 34 of 45 eyes (75.6%). The diagnoses were infectious uveitis in 13 eyes (28.9%), noninfectious uveitis in 21 eyes (46.7%), and unidentified uveitis in 11 eyes (24.4%). Visual acuity (VA) improvement rates at 6 months after surgery were 69.2%, 76.2%, and 90.9% in the infectious, noninfectious, and unidentified uveitis groups, with no significant difference among 3 groups. Significant decrease in inflammation score after vitrectomy was observed only in the infectious uveitis group. This study demonstrated that diagnostic vitrectomy for inflammatory eyes with VO of unknown etiology was effective in infectious and noninfectious uveitis, and the therapeutic effect of VA improvement was observed in both types of uveitis.